Rekonstruksi Hukum Kontrak Joint Venture dalam Menjamin Keseimbangan Hak dan Kewajiban Para Pihak pada Usaha Penanaman Modal di Indonesia - Nur Mutmainnah; Herman; Ahmaddin; Ronis; Ilyas (Jurnal Hukum Lex Generalis, 2026)
The increasing investment activities in Indonesia show a growing number of cooperation schemes between domestic and foreign investors in the form of joint venture contracts. In practice, this contract is not merely seen as a business instrument, but also as a legal framework that determines the relationship between the parties in the long term. On the other hand, the complexity of joint venture arrangements often raises issues concerning the balance of rights and obligations between the parties, particularly due to differences in bargaining power. This condition may lead to contractual unfairness if it is not properly regulated within the existing legal system. This study aims to analyze how the reconstruction of joint venture contract law can ensure a balance of rights and obligations between parties in investment activities in Indonesia. The research employs a normative juridical method with statutory and conceptual approaches, supported by an analysis of contract law doctrines and joint venture practices in investment agreements. The findings show that the regulation of joint venture contracts in Indonesia has not fully ensured a balanced position between the parties. On the one hand, the principle of freedom of contract provides broad space for parties to determine the content of their agreement. On the other hand, this freedom is often not matched by adequate protection for the weaker party. Moreover, the absence of clear standards governing the allocation of risks, profits, and responsibilities in joint venture contracts further contributes to imbalance in practice. Therefore, a reconstruction of joint venture contract law is needed through strengthening the principle of balance, affirming contractual justice, and harmonizing it with investment law principles. In this way, joint venture contracts will not only serve as business cooperation instruments but also provide fair legal certainty for all parties involved.